IMPLEMENTASI EDM dan RKAM di MADRASAH IBTIDAIYYAH MUHAMMADIYAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Kusyaeni, Kusyaeni (STAI Ma'had Aly Al-Hikam Malang, 2022)
The purpose of this study is to describe the Implementation of EDM and E-RKAM in Madrasah Ibtidaiyah Muhammadiyah Tangkisan Pos for the 2022/ 2023 Academic Year. This research use descriptive qualitative approach. The subject of this research is the head Madrasah, while the informants of this research are treasurer of the madrasa, the madrasah committee, and the foundation. Methods of data collection using observation, documentation, and interviews. Test the validity of the data using triangulation of sources and methods. Data analysis using Miles and Huberman’s interactive model begins with data collection. Data presentation, and drawing conclusions. From the result of this study it can be concluded: 1) In implementing EDM and e-RKAM, the MIM Tangkisan Pos has not involved all elements in the madrasa, secpecially the madrasah development team which is dominated by teachers. 2) After carrying out EDM and e-RKAM, the quality of the Madrasah Ibtidaiyah Muhammadiyah Tangkisan Pos has improved in the last two years. 3) The benefits of the implementation of the EDM and e-RKAM are: 1) EDM is the key in identifying the strengths and weaknesses of madrasa performance, the quality and quality of madrasas that will be used in preparing the RKAM are relevant to actual conditions, 2) The quality of education increasses along with the fulfillment of infrastructure madrasas, 3) teacher competence has increased.